Mulaprasada of the Harshnath Temple - Temples of India Project Team (Jio Institute, 2024)
The jangha or wall portions of the sanctum are nearly in ruins. The temple lacks the pitha but begins from a single plinth course. The vedibandha is damaged in some areas, but otherwise, it had kumbha with intricate udgama motifs, with a small central box carrying a figure.